Species diversity of water birds in Deepor Beel, Assam - Das, Jyotismita; PK, Saikia (Journal of Research in Biology, 2011)
Study has been carried out to assess the water bird diversity in Deepor Beel Ramsar site of Assam from March 2007 to March 2010. Study revealed the presence of 39 species of water birds belonging to 16 families. The family Anatidae represented highest of eight species followed by seven species in the family Ardeidae whereas other 14 species represented by rest of the family. However, there were marked variation of species abundance in different years of study, of which, the family Anatidae represented the highest abundant family throughout the study period. The analysis of species diversity index using Shannon diversity index showed that the diversity was highest during 3rd year study period. Study also highlighted the threat factors prevailing in the Deepor Beel Ramsar Site